Studi Kelayakan Bisnis, Aspek Pemasaran, Aspek Sumber Daya Manusia dan Aspek Lingkungan pada Pabrik Air Minum Bersih (PT. Bumi Daha Sejahtera) - Tiara Nahda Wati; Maulida Rahma; Siti Napisah; Beneta Salwa Salsabela; Muhammad Firliadi Noor Salim (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Clean drinking water is a basic necessity with increasing demand due to population growth and rising health awareness. This study aims to evaluate the business feasibility of PT. Bumi Daha Sejahtera in producing clean drinking water, focusing on three key aspects: marketing, human resources (HR), and environmental impact. The research employs a descriptive qualitative method, collecting data through interviews, observations, and document analysis. The findings reveal a significant market potential for drinking water in the company’s operational area with moderate competition levels. In terms of HR, the local workforce is sufficiently available and can enhance their competencies through training programs. From an environmental perspective, the company can minimize negative impacts by adopting eco-friendly technologies and complying with regulatory standards. The study concludes that PT. Bumi Daha Sejahtera’s business is feasible, provided that these aspects are managed sustainably. The implications of this research highlight the importance of implementing effective marketing strategies, continuous employee training, and proper environmental management to ensure business sustainability.